Influence of the apron parking stand management policy on aircraft and ground support equipment (GSE) gaseous emissions at airports - Sznajderman, Lucas (2021)
The purpose of this study is to analyze the concept of a hybrid apron with a fixed number of parking positions considering the management model influence for the average delay per aircraft and the gaseous emissions generated by aircraft and ground support equipment (GSE) altogether. The apron is studied based on two gate management models: in the first model, the aircraft are allocated in each gate due to operational factors only; in the second model, the rules of exclusive use of each gate according to the airline are included. The emissions generated by aircraft operations and that of their GSE (produced by the service and movements on the apron) are quantified and compared in the two gate management models: operation in the standard LTO cycle of the studied aircraft, GSE emissions have a similar relation with the compared gasses (NOx and CO), ranging between 1% and 3%. Further, if it compares the emissions between support vehicles and aircraft taking only into account the in-out taxiway, the relation between both CO sources shows similar values to those of the previous comparison, whereas NOx emissions produced by GSE reach an approximately 20%. The study considers different demand conditions obtained from the average day of the peak month of Aeroparque Jorge Newbery airport. Subsequently, through the SIMMOD PLUS software, the aircraft operations are simulated. The gates assignment and the arrival timetables are used as inputs for the GSE study due to an analytical model developed by us. Once the operational dimension is characterized and evaluated, the necessary data to quantify the gaseous emissions from the sources (Aircraft-GSE), based on the International Civil Aviation Organization (ICAO) guidelines, is obtained.